Implementation of Electronification Whistleblowing System Through the Application of Complaint Service Information at The Jombang Regency Inspectorate - Dwi Septaningsih, Rina; Mustofa, Amirul (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2025)
The implementation of the Electronic Whistleblowing (WBS) system through the Complaint Service Information System application at the Jombang Regency Inspectorate is an innovation to increase transparency, accountability, and effectiveness of government governance. This application makes it easy for the public and employees to submit complaints quickly, safely, and in a structured manner through an easily accessible digital system. The electronic-based reporting feature and real-time monitoring of report status accelerate the Inspectorate's response to various complaints received. This study uses a qualitative descriptive method with five main indicators: commitment, visibility, accessibility, simplicity, and speed of complaint handling. The results of the study showed a high level of respondent satisfaction, with an average positive assessment of above 75%, as well as increased employee work efficiency, accelerated complaint resolution, and public participation in monitoring public services. However, challenges such as low digital literacy in rural areas, internal resistance to transparency, and issues of reporter data security still need to be addressed. Optimizing this system requires a broader socialization strategy, increased digital literacy, and strengthened technology infrastructure and data security. With these steps, WBS electronification is expected to become a more inclusive, effective, and sustainable complaint system in supporting clean and responsive governance.